Pengaruh E-Service Quality Terhadap Kepuasan Konsumen Pengguna Aplikasi Ojek Online Maxim Di Kota Palembang - Sari, Citra Purnama; Puspasari, Mardiana; Afrilliana, Nadia (Jurnal Ilmu Manajemen, Bisnis dan Ekonomi, 2025)
The purpose of this study is to determine the influence of E-Service Quality simultaneously and partially on consumer satisfaction of Maxim online motorcycle taxi application users in Palembang City. This study uses 100 samples, the sampling technique uses nonprobability sampling technique by purposive sampling. This type of research is associative, the data used is primary data, the data collection technique used is a questionnaire. The analysis technique used is multiple linear regression analysis, F test, t test and coefficient of determination. The results of the analysis show that: there is an influence of e-service quality simultaneously on consumer satisfaction of Maxim online motorcycle taxi application users in Palembang City. While partially: 1) efficiency (X1) has a significant effect on consumer satisfaction. 2) system svailability (X2) has a significant effect on consumer satisfaction. 3) fulfillment (X3) has a significant effect on consumer satisfaction. 4) privacy (X4) does not have a significant effect on consumer satisfaction. 5) responsiveness (X5) has a significant effect on consumer satisfaction. 6) compensation (X6) has a significant effect on consumer satisfaction. 7) contact (X7) does not have a significant effect on consumer satisfaction.